To select the optimal immunohistochemical staining method for pigmented melanoma - Juan Lin; Zhijie You; Xin Chen (Scientific Reports)
Abstract Melanin granules may be difficult to distinguish from the brown reaction product of 3,3’-diaminobenzidine (DAB) in immunostaining. To identify a reliable immunostaining protocol for pigmented melanoma that preserves tissue integrity while enabling clear observation of antigen-antibody binding. Ki67 and the human melanoma black 45 (HMB45) immunostaining was performed on 30 pigmented melanoma specimens using three methods: (1) Unbleached control, (2) Bleached with 5% H₂O₂, (3) Alkaline Phosphatase–3-Amino-9-Ethylcarbazole (AP-AEC). Compared with the unbleached control, the coincidence rates of Ki67 and HMB45 expression in bleached with 5% H2O2 group were 90.9% and 86.4%, respectively, and the one in AP-AEC group were 81.8% and 90.9%, respectively. No significant differences (all p > 0.05) in Ki67 expression and HMB45 expression parameters (percentage, staining intensity and H-score) between bleached group vs. unbleached control and AP-AEC group vs. control across all comparative measured parameters. A 25% (4/16) tissue damage rate occurred in heavily pigmented specimens subjected to the bleaching group, and non-specific staining were observed in AP-AEC processed samples. For lightly pigmented melanoma, bleached with 5% H2O2 method optimally balanced tissue preservation and staining reliability. Non-specific immunostaining was observed in the AP-AEC group. For heavily pigmented melanoma, AP-AEC method minimized tissue damage despite minor non-specificity.